2012
DOI: 10.2203/dose-response.11-054.rattan
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis-Based Anti-Aging Products: A Case Study of a Novel Cosmetic

Abstract: ᮀ Application of hormesis in aging research and interventions is becoming increasingly attractive and successful. The reason for this is the realization that mild stress-induced activation of one or more stress response (SR) pathways, and its consequent stimulation of repair mechanisms, is effective in reducing the age-related accumulation of molecular damage. For example, repeated heat stress-induced synthesis of heat shock proteins has been shown to have a variety of anti-aging effects on growth and other ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…These dual roles of Hsp70-1A in determining pigmentation both in melanocytes and in keratinocytes were considered to be clearly reflected in Hsp70 inhibitor-driven skin lightening and Hsp70-1A activator-driven skin darkening in ex vivo skin tissues. In addition, it has been reported that overexpression of Hsp70-1A inhibited UV-induced epidermal hyperplasia, degradation of extracellular matrix, and decreased skin elasticity that would characterize skin photoaging in SKH-1 mice (Matsuda et al, 2013), which led several cosmetic and/or skin care companies to launch products that counteract UV-induced premature skin aging via the activation and/or increased expression of Hsp70-1A (Rattan et al, 2013). Taken together, Hsp70-1A would be an essential player in skin protection against UV exposure, not only through its known efficacy in repairing cellular damage but also its previously unreported roles in regulating multiple stages of pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…These dual roles of Hsp70-1A in determining pigmentation both in melanocytes and in keratinocytes were considered to be clearly reflected in Hsp70 inhibitor-driven skin lightening and Hsp70-1A activator-driven skin darkening in ex vivo skin tissues. In addition, it has been reported that overexpression of Hsp70-1A inhibited UV-induced epidermal hyperplasia, degradation of extracellular matrix, and decreased skin elasticity that would characterize skin photoaging in SKH-1 mice (Matsuda et al, 2013), which led several cosmetic and/or skin care companies to launch products that counteract UV-induced premature skin aging via the activation and/or increased expression of Hsp70-1A (Rattan et al, 2013). Taken together, Hsp70-1A would be an essential player in skin protection against UV exposure, not only through its known efficacy in repairing cellular damage but also its previously unreported roles in regulating multiple stages of pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Hormetins can strengthen the homeodynamics, increase robustness of the system and enhance resilience [29]. Just as in the case of exercise-induced hormetic benefits via heat shock protein synthesis, hormetins such as ginsenosides in the cosmeceutical formulations [48] may be considered as performing a kind of intracellular molecular exercise. Certain CR mimetics may prove to be effective hormetins acting via autophagic and sirtuin-dependent SR pathways [49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…An example of a successful skin care cosmetic product developed by incorporating the ideas of hormesis is based on the studies to analyse the molecular effects of active ingredients extracted from the roots of the Chinese herb Sanchi (Panax notoginseng) on gene expression at the level of mRNAs and proteins in human skin cells [48] The results showed that the ginsenosides extracted from Sanchi induced the transcription of stress genes and increased the synthesis of stress proteins, especially the heat shock protein HSP1A1 or Hsp70, in normal human keratinocytes and dermal fibroblasts. Furthermore, this extract also has significant positive effects against facial wrinkles and other symptoms of facial skin aging as tested clinically, which may be due to its hormetic mode of action by stress-induced synthesis of chaperones involved in protein repair and removal of abnormal proteins [48]. (also see: http://www.givenchybeauty.com/en/skincare/vaxin-for-youth/inspiration).…”
Section: Hormesis and Hormetins In Cosmeticsmentioning
confidence: 99%
“…Instead, they initially cause molecular damage by virtue of their electrochemical properties and have a typical biphasic hormetic dose response. Some examples of nutritional hormetins involving heat shock response (HSR) are phenolic acids, polyphenols, flavonoids, ferulic acid, geranylgeranyl, rosmarinic acid, kinetin, zinc, and the extracts of tea, dark chocolate, saffron and spinach [42]".…”
Section: Aging Interventions Stress and Hormesismentioning
confidence: 99%
“…Discovering novel hormetins by putting potential candidates through a screening process for their ability to induce one or more SR pathways in cells and organisms can be a promising strategy [42]. Recently, a general scheme for screening natural and synthetic single compounds or complex extracts for potentially hormetic use for human beings has been put forward [30].…”
Section: Aging Interventions Stress and Hormesismentioning
confidence: 99%